Genetic Variation in the Extended Major Histocompatibility Complex and Susceptibility to Childhood Acute Lymphoblastic Leukemia: A Review of the Evidence - Urayama, Kevin Y.; Thompson, Pamela D.; Taylor, Graham M.; Trachtenberg, Elizabeth A.; Chokkalingam, Anand P. (Frontiers in Oncology, 2013)
The enduring suspicion that infections and immunologic response may play a role in the etiology of childhood leukemia, particularly acute lymphoblastic leukemia (ALL), is now supported, albeit still indirectly, by numerous epidemiological studies. The cumulative evidence includes, for example, descriptive observations of a peculiar peak incidence at age 2-5 years for ALL in economically developed countries, clustering of cases in situations of population mixing associated with unusual patterns of personal contacts, associations with various proxy measures for immune modulatory exposures early in life, and genetic susceptibility conferred by variation in genes involved in the immune system. In this review, our focus is the extended major histocompatibility complex (xMHC), an approximately 7.6 megabase region that is well-known for its high density of expressed genes, extensive polymorphisms exhibiting complex linkage disequilibrium patterns, and its disproportionately large number of immune-related genes, including human leukocyte antigen (HLA). First discovered through the role they play in transplant rejection, the classical HLA class I (HLA-A, -B, and -C) and class II (HLA-DR, HLA-DQ, and HLA-DP) molecules reside at the epicenter of the immune response pathways and are now the targets of many disease susceptibility studies, including those for childhood leukemia. The genes encoding the HLA molecules are only a minority of the over 250 expressed genes in the xMHC, and a growing number of studies are beginning to evaluate other loci through targeted investigations or utilizing a mapping approach with a comprehensive screen of the entire region. Here, we review the current epidemiologic evidence available to date regarding genetic variation contained within this highly unique region of the genome and its relationship with childhood ALL risk.